Had it with meetings? In aviation, more gets done with four Team Facilitations - Ralph Eckhardt; Arne Schulke (IUBH Internationale Hochschule, 2019)
The paper focuses on meetings as an over-utilized, but often under-structured tool for managerial effectiveness and efficiency. The authors present four different meeting types, more precisely termed team facilitations, as commonly used in aviation by flight crews: Brainstorming, Briefing, Decision Meeting and Debriefing. In addition, the role of a facilitator is discussed and the importance of a "Comm Cadence" (structural and communicative rules for each facilitation) is put forth. It is suggested that each facilitation be used with a specific purpose, structure, set of attendants, timing etc., and argued towards their general usefulness beyond aviation in any contemporary business setting.
Keywords: M10; M11; M31; N70; 650; Aviation; Aviation; Time Management; Project Management; Meetings; Leadership; Agility